2002
DOI: 10.1161/01.hyp.0000039962.68332.59
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antioxidant Vitamins and Blood Pressure in the United States Population

Abstract: Abstract-Serum vitamin C has been inversely associated with blood pressure in several epidemiologic studies, but little is known about effect of other antioxidant vitamins. We examined the relation between serum vitamins A, C, and E, ␣-carotene, and ␤-carotene levels and blood pressure among 15 317 men and women Ն20 years of age who participated in the Third National Health and Nutrition Examination Survey. Blood pressure was characterized as the average of 6 measurements obtained over 2 visits by trained obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 34 publications
8
48
1
5
Order By: Relevance
“…We found no significant association between plasma levels of Vitamins A and E and hypertension status in comparison to the findings reported by Chen et al,14 in which these measures were strongly associated with having definite or probable hypertension, and diastolic and systolic BP. We have no adequate explanation for this discrepancy in the results, except for the fact that samples were quite different in ages, with our group being in the narrow age range of 60-64 years, whereas the NHANES III sample had a wide age range X20 years.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found no significant association between plasma levels of Vitamins A and E and hypertension status in comparison to the findings reported by Chen et al,14 in which these measures were strongly associated with having definite or probable hypertension, and diastolic and systolic BP. We have no adequate explanation for this discrepancy in the results, except for the fact that samples were quite different in ages, with our group being in the narrow age range of 60-64 years, whereas the NHANES III sample had a wide age range X20 years.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results offer some support for previously reported findings including those of Chen et al, 14 who found a significant association between b-carotene and hypertension in logistic regression analyses. In our study, we found b-carotene to be associated with both diastolic and systolic BP, findings that held for the multiple linear regression analyses although the amount of variation explained by b-carotene was relatively small.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…159 Antioxidant vitamins reduced blood pressure and arterial stiffness in patients with diabetes or hypertension in small clinical studies, 160 but had no effect in postmenopausal women, in healthy subjects or in pregnant women at risk for hypertension/preeclampsia. [159][160][161][162] …”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%
“…161,162 However, findings are inconsistent and clinical trial data are inconclusive. [163][164][165] In general results of clinical studies investigating cardiovascular effects of antioxidants have been disappointing given the consistent and promising findings from experimental investigations.…”
Section: Therapeutic Potential Of Ros Modulators In Hypertensionmentioning
confidence: 99%